Entre a lousa e o altar : a inserção da Magia Divina de Rubens Saraceni nos terreiros de umbanda no estado de São Paulo - Capelli, Carolina (2017)
The Umbanda´s history in Brazil is marked since its foundation by the intense publication of doctrinal and literary books written by different liturgical currents, also representatives of different political associations. Following the trajectory of one of the greatest Umbanda´s authors, this dissertation analyzes the emergence of a new chain of umbanda. Created by Rubens Saraceni in the late 90´s, the so called Divine Magic inserts in Umbanda´s terreiros the use of mandalas, giving to the old Umbanda´s symbols a new look, linked to the esoteric and modern urban movements. Reaching new audiences, the expansion of this new "energetic" Umbanda ", merges in terreiros the classroom and the altar. The integration of courses and practices of Divine Magic on the terreiros features various implications, such as the formation of a network of interconnected terreiros and the emergence of groups and representatives in order to strengthen and unify within the Umbanda. This effort of indoctrination and standardization of practices next to the insertion of a new conflict resolution´s key seems to offer us clues about the contemporary Umbanda movement itself, part of the religious Market is greater than the Umbanda itself.